РЕЛЕЙНО-ВЕКТОРНАЯ СИСТЕМА УПРАВЛЕНИЯ БЕСКОНТАКТНЫМИ ДВИГАТЕЛЯМИ С ПОСТОЯННЫМИ МАГНИТАМИ С ДАТЧИКОМ ТОКА В ЗВЕНЕ ПОСТОЯННОГО ТОКА - Акинин , К.П. (Інститут електродинаміки НАН України, Київ, 2014)
The subject of this paper is the relay vector stator currents control system of permanent magnet brushless motors equipped with DC link current sensor in two-stage frequency converter scheme and two-position relay regulator without hysteresis loop in current control system. The time duration of one nonzero voltage vector during modulation period is fixed at the moment of equality of reference signal and DC link current sensor signal. The time duration of other nonzero voltage vector is calculated on the basis of first pulse duration in accordance with the inverter voltage vector position. The proposed relay vector control approach provides maximum possible speed of response of stator currents control. Examples of motor currents computation are given. References 6, table 1, figures 3.